DESIGNING ENGLISH VISITING BANYUMAS APPLICATION TO PROMOTE TOURIST DESTINATIONS - Aliyah, Jannatin; Mariasari, Septi; Dodiyanto, Rosyid (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2021)
This job training report was entitled “Designing English Visiting Banyumas Application to Promote Tourist Destinations”. The writer conducted job training started on Monday, February 1st, 2021, to Sunday, February 28th, 2021. The purpose of implementing the job training was to help the Banyumas Tourism, Sport, and Youth Office create a tourism promotion strategy in digital form. Banyumas has many beautiful tourist objects that were still not widely known by the public. Therefore, an application called Visiting Banyumas was created. This android-based application was created to make it easier for the public to get complete information about tourist attractions that are effective, massive, fast, and cheap.The method of making this application used the Waterfall method. This method could also be referred to as a linear sequential model or a classical life cycle. The approach used was a software approach sequentially starting from analysis, design, construction, testing, and maintenance. The implementation of this job training resulted in the Visiting Banyumas application, which could be downloaded for free on the Google Play Store. Six important aspects in the application are tourist objects and their history, tourist villages, culture, art, culinary, tourism, admin phone numbers, accommodation, and directions. All of these aspects contained titles, photos, and complete explanations. The latest news is contained in the application. The bookmark feature in the application could also help users to more easily access the application. This application is expected to help attract tourists to visit the Banyumas area. In addition, this application also uses English, which could be easily accessed and understood by foreign tourists. That is way, it could increase the number of foreign tourists who wanted to enjoy some of the beautiful places in Banyumas.